Competitive State Anxiety Inventory-2 (CSAI-2): Evaluating the Swedish version by confirmatory factor analyses - Lundqvist, C.; Hassmen, P. (Journal of Sports Sciences, 2005)
A significant proportion of nutritional supplements manufactured worldwide contain non-listed contaminations with anabolic-androgenic steroids (AAS), whose ingestion may lead to positive doping test results. This will lead to the suspension of, and sanctions against, the athlete, since this group of active substances is prohibited by the anti-doping code of the World Anti-Doping Agency as well as by sports associations not connected with this agency. Considerable financial losses are often the consequence for a banned athlete. Based on an amendment to the law governing the manufacture and prescription of drugs (AMG) in Germany in 1997 and an increasingly extensive interpretation of the term "drug" by the Federal Supreme Court, preparations containing anabolic steroids or their precursors are to be classified as drugs and, therefore, are subject to compulsory declaration as stated by the AMG. If this obligation is not adhered to, the result may be a claim for damages by the athlete against the manufacturer of a preparation, if the athlete took the preparation thinking it was harmless as judged by the Anti-Doping regulations, but was then found to be positive in doping tests. The judges in the first case before the county court in Stuttgart decided in favour of the claim for damages with respect to lost bonuses, loss of earnings and accrued legal costs by a soccer player who tested positive and was therefore suspended. Based on the evidence presented, the court came to the decision that the soccer player's positive test result was due to the ingestion of nutritional supplements containing non-listed AAS. This procedure could set a precedent for other states to demonstrate that athletes who had tested positive due to contaminated nutritional supplements are not without legal protection.